A BRIEF ANALYSIS OF METHODS FOR CALCULATING THE FLOW RATE OF FLOW IN AN UNBOUND SOIL CHANNEL - Uzokova, Madina (Educational Research in Universal Sciences, 2024)
Based on the Ackers-White dependencies for determining sediment flow in stationary flows, a method for calculating sediment with an unsteady flow is proposed, taking into account the division of sediment into bottom and suspended, which relates to the calculation of sediment transport itself.